Condiciones para la formalización del sector floricultor del municipio de Cerinza, Boyacá. - Ojeda García, Oscar Javier (Universidad Antonio Nariño, 2021)
The main objective of this research article is to propose to entrepreneurs in the flower growing sector of the municipality of Cerinza, Boyacá, conditions for formalization that allow companies that are in informality to go into formality, through its application, since, it is essential to inquire about the causes for this phenomenon that is very high at the business level in the country, generating a problem that should have a greater degree of attention from the government, given that it is affecting both State, through the lower collection of taxes, as the workers of these establishments, since their working conditions are not ideal because they do not receive all the benefits to which they are entitled. The methodology used during the development of the research was the use of secondary sources of information such as: databases, indexed journal articles, degree theses, among others. The results of the research allow us to observe that business formalization brings a good number of benefits, such as: easier access to credit, increased tax collection by the State and working conditions that favor workers.